Development of a method for optimizing the site loading speed - Pushkar, Oleksandr; Hrabovskyi, Yevhen; Gordyeyev, Andriy (Eastern-European Journal of Enterprise Technologies, 2020)
We have proposed a method for optimizing the loading speed of the site. The site is targeted at the local audience within one city or region. It is also taken into account that we can develop the site in a ready-made content management system. We have formed a list of criteria that affect the site loading speed. Experts in multimedia publishing have been involved in forming a list of criteria that affect the site loading speed. We have discovered the difficulties and shortcomings of certain criteria, which should be considered as analytical and theoretical data for an expert review of the complexity of criteria implementation. The weighting factors of the criteria influence on the optimization degree of the website loading speed are determined. A pairwise comparison matrix of criteria is based on determining how much is one of the criteria influencing the optimization degree of the site loading speed more significant than the other. The calculation of the elements of the weighting matrix of the criteria is implemented. The most important and significant criteria that influence the optimization of the website loading speed have been discovered. We have formed an order of the criteria list implementation to increase the site loading speed. The implementation of the developed methodology for optimizing the site loading speed was implemented as a prototype of a food photographer's site, which is based on the Joomla 3.9 content management system (USA). We have reviewed several alternatives for the implementation of image compression. The site loading speed has been tested before and after the implementation of the developed method. It has been determined that, on average, site loading speed indicators improved by 48 %. The development of a method for optimizing the site loading speed will create conditions for improving the site's position in search engine rankings